2015
DOI: 10.2139/ssrn.3119692
|View full text |Cite
|
Sign up to set email alerts
|

Does Corruption Matter for Sources of Foreign Direct Investment?

Abstract: The paper provides a crosscountry empirical analysis of the impact of corruption on foreign direct investment flows. The gravity model augmented with joint effects of corruption in the origin and destination countries determines differentiated patterns of investment flows between countries with various level of control of corruption. The estimates point towards greater investment flows between countries with good control of corruption. Moreover, if control of corruption in the destination country improves, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Resolving the collinearity problem in their study resulted in a positive impact of institutions on FDI flows. Belgibayeva and Plekhanov (2015) find a negative linkage between corruption and FDI in a sample of developing and developed countries. Li and Resnick (2003) investigate the impact of democracy on FDI for a sample of 53 countries.…”
Section: Literature Reviewmentioning
confidence: 79%
See 1 more Smart Citation
“…Resolving the collinearity problem in their study resulted in a positive impact of institutions on FDI flows. Belgibayeva and Plekhanov (2015) find a negative linkage between corruption and FDI in a sample of developing and developed countries. Li and Resnick (2003) investigate the impact of democracy on FDI for a sample of 53 countries.…”
Section: Literature Reviewmentioning
confidence: 79%
“…However, the available literature scarcely discusses the importance of institutions in attracting FDI in South America. It is recognized in the literature that better institutions enhance the flow of FDI (Globerman and Shapiro, 2002), while the absence of quality institutions adversely affect the flow of investment (Belgibayeva and Plekhanov, 2015; Li and Resnick, 2003). Institutional quality matters to foreign investors because they lower the cost of doing business in host economies.…”
Section: Introductionmentioning
confidence: 99%
“…Developing countries with insignificant or low returns on foreign investment can benefit significantly from reducing corruption. Belgibayeva and Plekhanov (2015) concluded that improving corruption control in the destination country increases the flow of investment from countries with a lower incidence of corruption compared to countries with a higher incidence of corruption. The change in potential investor profile can further strengthen economic and political institutions that control corruption.…”
Section: Overview Of Previous Researchmentioning
confidence: 99%
“…Corruption in Latin America may have a diminishing effect on trade however exchange relationships involving corruption are not this straightforward (de Jong & Bogmans, 2011;Thede & Gustafson, 2012). Level of corruption does have an effect on which partners may be willing to trade (Belgibayeva & Plekhanov, 2019). Literature suggests that successful trading partners are those that are more familiar with and able to navigate a corrupt environment.…”
Section: Corruptionmentioning
confidence: 99%